Success in Initial Writing Learning in the Post-Covid-19 Pandemic: the Role of Teachers and Parents - Lelianasari; Vismaia S Damaianti (Jurnal Ilmiah Sekolah Dasar, 2024)
Initial writing skills in elementary schools provide opportunities for students to build a solid foundation in writing. However, many students in elementary schools’ experience difficulties in developing initial writing skills, such as recognizing letters, forming words, and constructing coherent sentences. Lack of training and effective teaching leads to low student interest and motivation to learn to write. This study aims to analyze the role of teachers and parents in the success of teaching initial writing for second grade of elementary school students after doing online learning activities due to the covid-19 outbreak. This research was studied using a qualitative research method with a case study design. This research is based on primary data, namely second grade students and teachers, secondary data are field teachers who teach in second grade and vice principals of curriculum areas. Data collection technique used is interview (in-depth interview), observation and documentation. The data analysis technique used is Milles and Huberman which consists of data reduction, data presentation, and data verification. Data credibility was also tested by means of triangulation of data sources. The research findings reveal that the first thing that needs to be understood in preparation for initial writing is students' motor readiness by continuing to practice writing pens, such as making straight lines, curves, etc. Teacher and parent assistance is optimized through WhatsApp Group by sharing educational videos about learning to write early. Appropriate teaching also gets good results with the ability of second grade of elementary school students to write meaningful and legible letters.